AN ANALYSIS OF FLOUTING MAXIM IN ISLAM MAKACHEV’S PRE-FIGHT AND POST FIGHT PRESS CONFERENCES UFC 302 - Hadianto, Muhammad Afif; Wuryandari, Dyah Ambar (Cahaya Ilmu Bangsa Institute, 2024)
Faculty Of Letters And Literature, Universitas GunadarmaLanguage is the most important element in human life. Language helps us to understand the world around us. Good communication must be applied so that miscommunication does not occur. The objectives of this study are to find out types or flouting maxims that are used in Islam Makachev’s press conference and to find out the most flouting maxim that occur in the press conference. This study used qualitative method to find data in Islam Makachev’s press conference UFC 302. This study found 22 data which consist of all 4 of the flouting maxims there are: Flouting Maxim of Quantity (9 data), Flouting Maxim of Quality (5 data), Flouting Maxim of Relation (6 data) and Flouting Maxim of Manner (2 data). Based on the data in this study, the most shown flouting maxim in Islam Makachev’s press conference is Flouting Maxim of Quantity with 9 dataKeywords : Flouting Maxim, Islam Makachev, Press Conference